Pharmacogenomic tests in Oncology - finding the right dose - Jeziel Basso; Gilberto Schwartsmann (Brazilian Journal of Oncology)
A pharmacogenetics/genomics (PGx) anticancer drug testing program is being developed by Kurtz and his group at the Brazilian National Cancer Institute (INCA). Drug -gene pairs were selected for PGx testing based on the presence of clinically validated PGx associations and the availability of international guidelines with PGx-informed dosing recommendations. Fluoropyrimidines-DPYD, irinotecan-UGT1A1 and thiopurines-TPMT/NUDT15 were initially included. The current estimation of anticancer therapy doses usually does not reflect the complexities of metabolism. Therefore, efforts should be made in order to refine the ways we prescribe these drugs, being conventional cytotoxic or newer ones. This program is extremely welcome and may lead to more multi-institutional partnerships and should bring a broader discussion on the use of PGx and pharmacokinetics in routine oncology practice.